2020
DOI: 10.3389/fphar.2020.01060
|View full text |Cite
|
Sign up to set email alerts
|

The rCC16 Protein Protects Against LPS-Induced Cell Apoptosis and Inflammatory Responses in Human Lung Pneumocytes

Abstract: Objective Our previous clinical study showed that low lung levels of CC16 strongly influence the occurrence and development of ARDS. The aim of the present study was to evaluate the therapeutic effect of rCC16 on LPS-induced inflammation in A549 cells and to determine its mechanism. Methods Cell apoptosis and inflammation was induced by LPS stimulation. The cytotoxic effect of rCC16 was evaluated using the MTT assay. Cytokine levels were determined using enzyme-linked i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…Pang et al also showed that 5 µg/mL rCC16 inhibits the expressions of TNF-α, IL-6, and IL-8 in LPS-treated RAW264.7 cells via NF-κB and p38 MAPK pathways [ 31 ]. In lung epithelial cells, a recent study found that rCC16 protects against LPS-induced apoptosis and inflammatory responses in A549 cells [ 49 ]. However, rCC16 was provided in supraphysiological concentrations, which range from 50 to 200 μg/mL.…”
Section: Discussionmentioning
confidence: 99%
“…Pang et al also showed that 5 µg/mL rCC16 inhibits the expressions of TNF-α, IL-6, and IL-8 in LPS-treated RAW264.7 cells via NF-κB and p38 MAPK pathways [ 31 ]. In lung epithelial cells, a recent study found that rCC16 protects against LPS-induced apoptosis and inflammatory responses in A549 cells [ 49 ]. However, rCC16 was provided in supraphysiological concentrations, which range from 50 to 200 μg/mL.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that there are physiological interrelations between some of the investigated biomarkers and traditional indicators. Evidence from our previous research 19 and other 20,21 suggests that CC16 positively correlates with Scr, Lac and NT-proBNP. This might related to the anti-inflammatory function, immune system activation, and lactate metabolism pathway related to prephosphorylation.…”
Section: Discussionmentioning
confidence: 67%
“…The PI3K/Akt signaling pathway regulates the release of inflammatory transmitters in inflammatory response in the lungs and airways (49). The latest studies demonstrated that during the SARS-CoV-2 infection, the PI3K/Akt/ mTOR pathway was activated in a dose-dependent manner which activated cell apoptosis process (50).…”
Section: Discussionmentioning
confidence: 99%